Optimization of Link & Match in the Instructional Design Process for Students with Intellectual Disability - Effendi, Zulfa Rahmah; Septiana, Fajar Indra; Ridwan, Prinanda Gustarina; Mastiani, Emay; Sudiarsa, Andri (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
Teaching materials that are prepared based on the actual conditions of students are one aspect that needs to be underlined so that students can actively participate in learning. This research took place at SLB ABC YPLAB Lembang, West Bandung Regency, and aims to produce teaching materials that are student center for students with intellectual disabilities in early grades. The focus of this research is on the adjustment stage between student profiles and curriculum content, where the link & match process between student assessment results and the curriculum becomes the basis for the instructional design process. The method used in this research is qualitative descriptive. There are four stages carried out, encompass initial assessment of basic abilities, reviewing curriculum content, matching student profiles with the curriculum, curriculum modification, and preparation of teaching materials. The results of this study are teaching materials that are student center to accommodate the conditions, potential, and learning characteristics of students with intellectual disabilities.